(untitled) (Филологические заметки, 2019)
Psycholinguistics horizons are stretched far beyond this science. The method of associative experiment applied in traditional linguistics, cognitive linguistics etc is especially popular. In article describes experiment in which the concept “Love” is recreated by means of an associative method. Actual meanings of the concept are represented in the cognition of male and female citizens of two age groups (till 35 years and after 35 years).